Docsity
Docsity

Prepare for your exams
Prepare for your exams

Study with the several resources on Docsity


Earn points to download
Earn points to download

Earn points by helping other students or get them with a premium plan


Guidelines and tips
Guidelines and tips

Vector Algebra - Calculus II - Lecture Slides | MATH 114, Study notes of Mathematics

Material Type: Notes; Professor: So; Class: CALCULUS II; Subject: Mathematics; University: University of Pennsylvania; Term: Fall 2009;

Typology: Study notes

2009/2010

Uploaded on 03/28/2010

koofers-user-9ep
koofers-user-9ep 🇺🇸

3.5

(1)

10 documents

1 / 66

Toggle sidebar

Related documents


Partial preview of the text

Download Vector Algebra - Calculus II - Lecture Slides | MATH 114 and more Study notes Mathematics in PDF only on Docsity!

Math 114-004, Fall 2009

Tong Zhu

Department of Mathematics University of Pennsylvania

September 24, 2009

Vector Algebra

I (^) Vector Addition

I (^) Scalar Multiplication

Vector Algebra

I (^) Vector Addition

I (^) Scalar Multiplication

I (^) How about the product of two vectors?

Vector Algebra

I (^) Vector Addition

I (^) Scalar Multiplication

I (^) How about the product of two vectors?

  1. Dot Product ~v · ~u
  2. Cross Product ~v × ~u

Before the geometry,

Determinant

Before the geometry,

Determinant

I (^) Determinant of a 2 × 2 matrix,

a b

c d

∣ =^ ad^ −^ bc

I (^) Determinant of a 3 × 3 matrix,

∣ ∣ ∣ ∣ ∣ ∣

a 1 a 2 a 3

b 1 b 2 b 3

c 1 c 2 c 3

∣ ∣ ∣ ∣ ∣ ∣

= a 1

b 2 b 3

c 2 c 3

− a 2

b 1 b 3

c 1 c 3

  • a 3

b 1 b 2

c 1 c 2

=a 1 (b 2 c 3 − b 3 c 2 ) − a 2 (b 1 c 3 − b 3 c 1 ) + a 3 (b 1 c 2 − b 2 c 1 )

Example 1

1. ∣

− 1 2

Example 1

1. ∣

− 1 2

= − 5 − 6 = − 11

Example 1

1. ∣

− 1 2

= − 5 − 6 = − 11

∣ ∣ ∣ ∣ ∣ ∣

− 1 3 5

∣ ∣ ∣ ∣ ∣ ∣

= 2

− 4

− 1 5

− 1 3

=2(18 − 10) − 4(− 6 − 35) + 6(− 2 − 21) = 42

Example 1

1. ∣

− 1 2

= − 5 − 6 = − 11

∣ ∣ ∣ ∣ ∣ ∣

− 1 3 5

∣ ∣ ∣ ∣ ∣ ∣

= 2

− 4

− 1 5

− 1 3

=2(18 − 10) − 4(− 6 − 35) + 6(− 2 − 21) = 42

∣ ∣ ∣ ∣ ∣ ∣

− 1 3 5

− 1 3 5

∣ ∣ ∣ ∣ ∣ ∣

= 2

− 4

− 1 5

− 1 5

− 1 3

− 1 3

= 0

Cross Product

In 3-D,

Definition If two vectors ~a =< a 1 , a 2 , a 3 > and ~b =< b 1 , b 2 , b 3 >,

then the cross product of ~a and ~b is defined as

~a × ~b =< a 2 b 3 − a 3 b 2 , a 3 b 1 − a 1 b 3 , a 1 b 2 − a 2 b 1 >

Cross Product

In 3-D,

Definition If two vectors ~a =< a 1 , a 2 , a 3 > and ~b =< b 1 , b 2 , b 3 >,

then the cross product of ~a and ~b is defined as

~a × ~b =< a 2 b 3 − a 3 b 2 , a 3 b 1 − a 1 b 3 , a 1 b 2 − a 2 b 1 >

Remark: Cross product gives a vector.

Cross Product

In 3-D,

Definition If two vectors ~a =< a 1 , a 2 , a 3 > and ~b =< b 1 , b 2 , b 3 >,

then the cross product of ~a and ~b is defined as

~a × ~b =< a 2 b 3 − a 3 b 2 , a 3 b 1 − a 1 b 3 , a 1 b 2 − a 2 b 1 >

Remark: Cross product gives a vector.

But the components of this vector is hard to memorize. There

must be a neat formula!

By the notation of determinant, if ~a =< a 1 , a 2 , a 3 > and

~b =< b 1 ,^ b 2 ,^ b 3 >,

~a × ~b =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

b 1 b 2 b 3

∣ ∣ ∣ ∣ ∣ ∣

Example ~a =< 2 , 3 , 4 >, ~b =< 1 , 5 , − 6 >

By the notation of determinant, if ~a =< a 1 , a 2 , a 3 > and

~b =< b 1 ,^ b 2 ,^ b 3 >,

~a × ~b =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

b 1 b 2 b 3

∣ ∣ ∣ ∣ ∣ ∣

Example ~a =< 2 , 3 , 4 >, ~b =< 1 , 5 , − 6 >

~a × ~b =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

1 5 − 6

∣ ∣ ∣ ∣ ∣ ∣ =

5 − 6

~i −

1 − 6

~j +

~k

= − 38 ~i + 16~j + 7~k

Some properties of cross product:

I (^) ~a × ~a = ~ 0

Some properties of cross product:

I (^) ~a × ~a = ~ 0

~a × ~a =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

a 1 a 2 a 3

∣ ∣ ∣ ∣ ∣ ∣

= ~ 0

Some properties of cross product:

I (^) ~a × ~a = ~ 0

~a × ~a =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

a 1 a 2 a 3

∣ ∣ ∣ ∣ ∣ ∣

= ~ 0

I (^) ~a × ~b = −~b × ~a

Some properties of cross product:

I (^) ~a × ~a = ~ 0

~a × ~a =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

a 1 a 2 a 3

∣ ∣ ∣ ∣ ∣ ∣

= ~ 0

I (^) ~a × ~b = −~b × ~a

~a × ~b =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

a 1 a 2 a 3

b 1 b 2 b 3

∣ ∣ ∣ ∣ ∣ ∣

=

a 2 a 3

b 2 b 3

~i −

a 1 a 3

b 1 b 3

~j +

a 1 a 2

b 1 b 2

~k

~b × ~a =

∣ ∣ ∣ ∣ ∣ ∣

~i ~j ~k

b 1 b 2 b 3

a 1 a 2 a 3

∣ ∣ ∣ ∣ ∣ ∣

=

b 2 b 3

a 2 a 3

~i −

b 1 b 3

a 1 a 3

~j +

b 1 b 2

a 1 a 2

~k

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) ~a × (~b + ~c) = ~a × ~b + ~a × ~c

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) ~a × (~b + ~c) = ~a × ~b + ~a × ~c

I (^) (~a + ~b) × ~c = ~a × ~c + ~b × ~c

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) ~a × (~b + ~c) = ~a × ~b + ~a × ~c

I (^) (~a + ~b) × ~c = ~a × ~c + ~b × ~c

I (^) ~a · (~b × ~c) = (~a × ~b) · ~c

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) ~a × (~b + ~c) = ~a × ~b + ~a × ~c

I (^) (~a + ~b) × ~c = ~a × ~c + ~b × ~c

I (^) ~a · (~b × ~c) = (~a × ~b) · ~c

Proof : Method 1: algebraic way

I (^) (c~a) × ~b = c(~a × ~b) = ~a × (c~b)

I (^) ~a × (~b + ~c) = ~a × ~b + ~a × ~c

I (^) (~a + ~b) × ~c = ~a × ~c + ~b × ~c

I (^) ~a · (~b × ~c) = (~a × ~b) · ~c

Proof : Method 1: algebraic way

Method 2:

~a · (~b × ~c) =

∣ ∣ ∣ ∣ ∣ ∣

a 1 a 2 a 3

b 1 b 2 b 3

c 1 c 2 c 3

∣ ∣ ∣ ∣ ∣ ∣